Measuring Koffielosophy Performance by Using Marketing MIX and Dimensions of Service Quality - Fakhrizal, Muhammad; Wandebori, Harimukti (Journal of Business and Management, 2013)
Coffee shops can be found in many different corners in Bandung. One of the coffee shops located in Bandung is Koffielosophy. It is important for the coffee shop management to find out what are they missing in performing a coffee shop by assessing the problems from all aspects and finding the solution to improve the services given. To assess this problem researcher used 4P Marketing Mix and RATER Service Quality. Researcher conducted interview and questionnaires with likert scaling. The data gathered were then analyzed with frequency analysis and SWOT analysis. Based on the data analyzed, the variables of problems that the coffee shop suffers and creates customers dissatisfaction are promotion and advertising. The strategic location and good tangible services has become the variables that the coffee shop is very proud of. From the factor analysis, researcher concluded that there are 6 factors to be considered for the coffee shop, promotion, reliability, price, empathy, product, and responsiveness.Â Keywords- coffee shop, performance, 4P marketing mix, RATER, service quality, frequency analysis, SWOT analysis---------------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.Â Â